La Maleta de Tesoros - Sylvester, Natalia; Medina, Juana, 1980- (New York : Dial Books for Young Readers, 2024)
"When Abuela comes to visit from Peru, she brings a suitcase full of treasures and her granddaughter learns that home is not just a place, but the love between family no matter the distance"--
Keywords: Grandmothers -- Fiction; Peruvian Americans -- Fiction; Spanish language materials; Picture books